Code-switching as a communicative tool in the classroom interaction of ED2203B B.Ed TESL students at the Faculty of Education, UiTM Shah Alam: a case study / Nik Mastura Nik Ismail Azlan - Nik Ismail Azlan, Nik Mastura (2011)
Many studies have been conducted by linguistic experts on the phenomenal functions of code-switching in the instructional contexts of the second language. Research has found many different aspects of code-switching studied in language classrooms. This research sought to investigate how code-switching is used as a communicative tool in the classroom interaction of ED2203B B.Ed TESL students in UiTM Shah Alam. A survey, observations and interviews were carried out to elicit relevant data. Quantitative data was analyzed using the statistical software, SPSS 17.0. Data was analyzed and presented in percentages and mean scores. Qualitative data was collected using an observational framework adapted from Greggio, S. and Gil, G. (2007) and each situation for code-switching was analyzed based on the 10 reasons provided by Muthusamy (2009). The findings revealed that three types of code-switching known as tag switching, inter-sentential switching and inter-sentential switching were used by the respondents. In addition, the 10 reasons of codeswitching adapted from the study by Muthusamy (2009) were found to be used in all five of the observations conducted in the language classroom. In addition to this, English was the dominant language used by the TESL students in most classroom situations. Students were also found to be frequent users of code-switching among their friends and with their lecturer. These findings implicated that while code-switching was a useful communicative tool, too much code-switching could lead to overdependence on the strategy.